The implementation of campus bookstore management system integrated with WhatsApp and Google Services / Mohd Nizam Osman ... [et al.] - Osman, Mohd Nizam; Othman, Nor Arzami; Sedek, Khairul Anwar; Ahmad, Amir Imran; Maghribi, Mushahadah (UiTM Cawangan Perlis, 2024)
Campusbookstore management system integrated with WhatsApp and Google services is a new approach of the web-based development project, especially for students to purchase and sell vast quantities of books, mainly used books. This approach helps students obtain books quicker and more cheaply. The proposed system utilized Googleservices such as email, Google form and Google spreadsheet. WhileWhatsApp allows communication between admin and users for any transaction made. Meanwhile, ToyyibPay payment gateway lets students purchase books online without cash. Two experiments were conducted to evaluate the effectiveness of the system which is usability testing and network performance test. A usability testing was done with 30 respondents to assess the efficacy of the system by reviewing questionnaires, which was categorized into 4 categories included user interface satisfaction, usefulness and ease of use, usability of the system, and WhatsApp and Google services integration. The findings indicated most respondents were satisfied and positively accepted the proposed system. Meanwhile, the result of network performance on the website speed test for mobile and desktop devices was satisfactory. Therefore, it is a practical, cost-effective, trustworthy option that can help students in book sales transactions and subsequently can generate additional income for students.